The 5S rDNA family evolves through concerted and birth-and-death evolution in fish genomes: an example from freshwater stingrays - Pinhal, Danillo [UNESP]; Yoshimura, Tatiana S. [UNESP]; Araki, Carlos S. [UNESP]; Martins, Cesar [UNESP] (Biomed Central Ltd., 2011)
Background: Ribosomal 5S genes are well known for the critical role they play in ribosome folding and functionality. These genes are thought to evolve in a concerted fashion, with high rates of homogenization of gene copies. However, the majority of previous analyses regarding the evolutionary process of rDNA repeats were conducted in invertebrates and plants. Studies have also been conducted on vertebrates, but these analyses were usually restricted to the 18S, 5.8S and 28S rRNA genes. The recent identification of divergent 5S rRNA gene paralogs in the genomes of elasmobranches and teleost fishes indicate that the eukaryotic 5S rRNA gene family has a more complex genomic organization than previously thought. The availability of new sequence data from lower vertebrates such as teleosts and elasmobranches enables an enhanced evolutionary characterization of 5S rDNA among vertebrates.Results: We identified two variant classes of 5S rDNA sequences in the genomes of Potamotrygonidae stingrays, similar to the genomes of other vertebrates. One class of 5S rRNA genes was shared only by elasmobranches. A broad comparative survey among 100 vertebrate species suggests that the 5S rRNA gene variants in fishes originated from rounds of genome duplication. These variants were then maintained or eliminated by birth-and-death mechanisms, under intense purifying selection. Clustered multiple copies of 5S rDNA variants could have arisen due to unequal crossing over mechanisms. Simultaneously, the distinct genome clusters were independently homogenized, resulting in the maintenance of clusters of highly similar repeats through concerted evolution.Conclusions: We believe that 5S rDNA molecular evolution in fish genomes is driven by a mixed mechanism that integrates birth-and-death and concerted evolution.